Формирование толерантной личности на занятиях по английскому языку - Пономарева, Е.А.; Молдакаликова, А.А.; Буранова, А.Б. (My University, 2016)
The idea of tolerance development is determined by the modern social order of student training to the future professional activity. It is necessary to study this problem, its scientific status determination, searching the ways of tolerance development in the process of “Practical English grammar” studying
Keywords: tolerance; interaction; intolerant behavior; up-bringing process; educational process